Initiation of Supporting Cell Activation for Hair Cell Regeneration in the Avian Auditory Epithelium: An Explant Culture Model - Matsunaga, Mami; Kita, Tomoko; Yamamoto, Ryosuke; Yamamoto, Norio; Okano, Takayuki; Omori, Koichi; Sakamoto, Satoko; Nakagawa, Takayuki (Frontiers in Cellular Neuroscience, 2020)
Sensorineural hearing loss is a common disability often caused by the loss of sensory hair cells in the cochlea. Hair cell regeneration has long been the main target for the development of novel therapeutics for sensorineural hearing loss. In the mammalian cochlea, hair cell regeneration is limited, but the auditory epithelia of non-mammalian organisms retain the capacity for hair cell regeneration. In the avian basilar papilla, supporting cells, which give rise to regenerated hair cells, are usually quiescent. Hair cell loss induces both direct transdifferentiation and mitotic division of supporting cells. Here, we established an explant culture model for hair cell regeneration in chick basilar papillae and validated it for investigating the initial phase of hair cell regeneration. Histological assessment demonstrated hair cell regeneration via direct transdifferentiation of supporting cells. Labeling with 5-ethynyl-2'-deoxyuridine (EdU) revealed the occurrence of mitotic division in the supporting cells at specific locations in the basilar papillae, while no EdU labeling was observed in newly generated hair cells. RNA sequencing indicated alterations in known signaling pathways associated with hair cell regeneration, consistent with previous findings. In addition, unbiased analyses of RNA sequencing data revealed novel genes and signaling pathways that may be related to the induction of supporting cell activation in the chick basilar papillae. These results indicate the advantages of our explant culture model of the chick basilar papillae for exploring the molecular mechanisms of hair cell regeneration.